Implementation Of Smartphone As Smart Security Based On Cloud Storage - Gufron, Gufron (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2024)
Security is one of the important aspects in everyday life, both in personal and professional contexts, especially in protecting property from the threat of theft, vandalism, and other criminal activities. For this reason, many parties install surveillance systems such as CCTV. However, traditional CCTV with local storage such as hard disks or DVRs has weaknesses, especially because it is vulnerable to physical damage by criminals. Along with the development of information and communication technology, access to CCTV equipment has also developed from cables to Wi-Fi, and storage media has been replaced with smaller SD cards. However, weaknesses related to physical damage to storage media still exist. To overcome this, the use of smartphones as security tools is now increasingly popular. Equipped with high computing capabilities, various sensors, quality cameras, and good internet connectivity, smartphones can be turned into security devices that can monitor situations in real-time and upload recordings directly to cloud storage, so they are safe from attempts to damage or theft of physical devices. Users can also access recordings at any time via the internet, increasing flexibility and convenience in maintaining the security of their property. This study uses a descriptive approach with a case study method to examine the implementation of smartphones as intelligent security systems based on cloud storage. Based on the results of the implementation and testing conducted, the use of smartphones has proven effective in supporting active security monitoring and management. The use of built-in sensors on smartphones allows for fast and accurate threat detection, while integration with cloud storage provides secure, flexible, and easily accessible storage. Thus, the combination of smartphones and cloud storage can be a solution for modern security needs.